Examining the knowledge gap of undergraduates awareness of the consumer protection act 1999 in relation to influencer marketing - Lim, Jia Yu (2025)
The rapid growth of influencer marketing on social media platforms has significantly shaped consumer behaviour, particularly among undergraduates who are active digital consumers. Despite this development, awareness of consumer rights under the Consumer Protection Act 1999 remains uncertain. This study aims to examine the knowledge gap among undergraduates regarding consumer protection in the context of influencer marketing in Malaysia.